Technical and economic evaluation of a solar thermal MgO electrolysis process for magnesium production. (15th September 2017) - Korenko, M.; Larson, C.; Blood, K.; Palumbo, R.; Nudehi, S.; Diver, R.; Blood, D.; Šimko, F.; Venstrom, L.J.
Abstract: We present a techno-economic analysis of a 17, 000–18, 000 metric tons per year electrolytic process for producing Mg from MgO with and without out a concentrated solar thermal input. The solar thermal input is delivered via power tower technology and the evaporation and condensation of sodium. Energy requirements for the process at scale were based on thermodynamics and an extrapolation of laboratory measurements of the electrochemical kinetic and mass transport parameters via a finite-element numerical model. While technically possible, integrating a solar thermal input does not make economic sense without crediting avoided CO2 emissions. A solar thermal input reduces energy operational costs from $0.654/kg to as low as $ 0.481/kg, but it also lowers the Mg production rate of the electrolytic cells such that more cells are required to achieve production capacity, which, in turn, increases capital and maintenance costs. The net operational savings are negligible. The estimated operational costs to produce Mg are ∼$2.46/kg. At this cost, the process without a solar thermal input is economically tantalizing vis à vis the current commercial processes for producing Mg, and its CO2 emission level is 46% lower than that of the Pidgeon process, currently the predominant method for producing Mg. Highlights: Model of an industrial-scale MgO electrolysis cell using detailed chemical kinetics. Identify cell voltage at which CF4 forms; it is below industrial operating voltages. Show that anode effect can be avoided in industrial MgO electrolysis. Concept couples concentrated solar radiation to industrial MgO electrolysis. Economic study of MgO electrolysis at scale with and without solar thermal input.